Message Packaging Strategy in the Gemarikan Campaign at the Marine and Fisheries Service of Lampung Province - Gregorius Manuel Jaya (KONTEKSTUAL : Jurnal Ilmu Komunikasi, 2026)
Lampung Province is one of the provinces with the lowest fish consumption rate in Indonesia, ranking 21st with a consumption rate of only 38.83 kg/year, far below the ideal rate of 62.5 kg/year set by the government. This condition is influenced by the lack of public understanding of the nutritional benefits of fish, limited facilities and infrastructure, and negative myths circulating in society, so the Marine and Fisheries Service of Lampung Province carries out the Fish-Eating Movement campaign. This study aims to describe the message packaging strategy in the Gemarikan campaign program at the Marine and Fisheries Service of Lampung Province. This study used a qualitative approach with a descriptive qualitative type, with triangulated data collection of in-depth interviews, observation, and documentation involving key, main, and supporting informants. Results show that the message packaging strategy was carried out in a planned manner and involved cross-division coordination with different but mutually supportive roles. The Gemarikan message was packaged using simple, easily understood language, adjusted to the needs of target groups such as schoolchildren, housewives, and posyandu, and reinforced through songs, educational videos, and fish-processing demonstrations. These findings show that the strategy applied the interrelated principles of source, message, channel, and receiver in delivering the campaign message.Key words: campaign, communication strategy, Gemarikan, message packaging, source credibility